Military strategies for sustainment of nutrition and immune function in the field (National Academy Press, 1999)
Every aspect of immune function and host defense is dependent upon a proper supply and balance of nutrients. Severe malnutrition can cause significant alteration in immune response, but even subclinical deficits may be associated with an impaired immune response, and an increased risk of infection. Infectious diseases have accounted for more off-duty days during major wars than combat wounds or nonbattle injuries. Combined stressors may reduce the normal ability of soldiers to resist pathogens, increase their susceptibility to biological warfare agents, and reduce the effectiveness of vaccines intended to protect them. There is also a concern with the inappropriate use of dietary supplements. This book, one of a series, examines the impact of various types of stressors and the role of specific dietary nutrients in maintaining immune function of military personnel in the field. It reviews the impact of compromised nutrition status on immune function; the interaction of health, exercise, and stress (both physical and psychological) in immune function; and the role of nutritional supplements and newer biotechnology methods reported to enhance immune function. The first part of the book contains the committee's workshop summary and evaluation of ongoing research by Army scientists on immune status in special forces troops, responses to the Army's questions, conclusions, and recommendations. The rest of the book contains papers contributed by workshop speakers, grouped under such broad topics as an introduction to what is known about immune function, the assessment of immune function, the effect of nutrition, and the relation between the many and varied stresses encountered by military personnel and their effect on health.